An Economy-Climate Model for Quantitatively Projecting the Impact of Future Climate Change and Its Application - Chou, Jieming; Xu, Yuan; Dong, Wenjie; Zhao, Weixing; Li, Jiangnan; Li, Yuanmeng (Frontiers in Physics, 2021)
Quantitatively projecting the impact of future climate change on the socio-economy and exploring its internal mechanism are of great practical significance to adapt to climate change and prevent climate risks. Based on the economy-climate (C-D-C) model, this paper introduces a yield impact of climate change (YICC) model that can quantitatively project the climate change impact. The model is based on the YICC as its core concept and uses the impact ratio of climate change (IRCC) indicator to assess the response of the economic system to climate change over a long period of time. The YICC is defined as the difference between the economic output under changing climate condition and that under assumed invariant climate condition. The IRCC not only reflects the sensitivity of economic output to climate change but also reveals the mechanism of the nonlinear interaction between climate change and non-climatic factors on the socio-economic system. Using the main grain-producing areas in China as a case study, we use the prediction data of the ensemble average of 5 GCMs in CMIP6 to project the possible impact of climate change on production in the next 15 to 30 years under three future scenarios. The results indicate that the long-term climate change in the future will have a restraining effect on production in North region and enhance production in South region. From 2021 to 2035, climate change will reduce production by 0.60% to 2.09% in North region, and increase production by 1.80% to 9.01% in South region under three future scenarios. From 2021 to 2050, compared with the climate change impact in 2021 2035, the negative impact of climate change on production in North region will weaken with the increase in emission concentration, and the positive impact on production in South region will enhance with the emission concentration. Among them, climate change will reduce grain output in North region by 0.52% 1.99%, and increase grain output in South region by 1.35% 9.56% under the three future scenarios. The combination of economic results and climate change research is expected to provide scientific support for further revealing the economic mechanism of climate change impacts.